Efektivitas Bahan Pelapis Benih terhadap Penyerapan Fosfat dan Pertumbuhan Bibit Kelapa Sawit - ,, Saipulloh; Palupi, Endah Retno; Widajati, Eny; Mathius, dan Nurita Toruan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
One way of overcome phosphate deficiency in oil palm plantation is seed enrichment using phosphate solvent microbes. This technique is expected to accelerate phosphate availability for plant. The aim of the research was to identify the best coating materials for seed enrichment that compatible with Burkholderia sp. in order to increase phosphate absorption, seed storability, and growth of oil palm seedlings. This research consisted of two consecutive experiments. The first experiment was arranged in randomized block design, with nine treatments of different seed coating materials. The second experiment was arranged in nested design, with main factor of 11 different seed coating materials and nested factors were five storage periods. The data was collected on growth parameters of seedling height, root length, trunk height, dry weight; phosphate absorption, and DGGE analysis. The research showed there were three best seed coating materials of CMC 1.5%, CMC 2% + gypsum 1.5%, and CMC 1.5% + talc 1%. The coating material enhances seedling growth and phosphate absorption. Seed coating and enrichment maintained seedling vigor for three days in the storage. Keywords: Burkholderia sp., carboxyl methyl cellulose, phosphate solvent microbial, seed enrichment, seed storage